An Indian global ethics initiative - Motilal, Shashi (Journal of global ethics, 2019)
In what sense must global ethics be global? In one sense, it must deal with global issues. In another, it must not be parochial but inclusive of normative views from around the world. So far, global ethics has met the first standard much better than the second. Authors based in the global South contribute approximately 5% of the internationally published research on global ethics. With this in mind, the co-editors of this special issue sought to bring more perspectives, experiences, and authors from India into the international global ethics conversation, and so they launched the Indian Global Ethics Initiative. Their first step, this special issue, presents Indian experience and authors on topics including urban development, care ethics, women’s empowerment, fair trade, distorted policy research, poverty, and health. Much of this work is grounded by the authors’ experience in policy-making and advocacy for social and global justice. The co-editors invite contact from interested readers who would like to join and continue this Indian Global Ethics Initiative, as well as readers who would like to take similar initiatives in other regions.